Synthesis, characterization and anticancer evaluation of transplatin derivatives with heterocyclic thiones. (15th February 2018) - Jomaa, Mohammed Y.; Altaf, Muhammad; Ahmad, Saeed; Alhoshani, Ali; Baig, Nadeem; Kawde, Abdel-Nasser; Bhatia, Gaurav; Singh, Jatinder; Isab, Anvarhusein A.
Graphical abstract: Platinum(II) complexes of heterocyclic thiones based on transplatin having the general formula, trans -[Pt(NH3 )2 (Thione)2 ].2NO3 have been synthesized and characterized using elemental analysis, IR, and NMR ( 1 H & 13 C) spectroscopy. The crystal structures of two of them, trans -[Pt(NH3 )2 (Imt)2 ].2NO3 and trans -[Pt(NH3 )2 (Me2 Imt)2 ].2NO3 were determined by X-ray crystallography. Abstract: Platinum(II) complexes of heterocyclic thiones (L) based on transplatin having the general formula, trans -[Pt(NH3 )2 (Thione)2 ](NO3 )2 have been synthesized and characterized using elemental analysis, IR, and NMR ( 1 H & 13 C) spectroscopy. The crystal structures of two of them, trans -[Pt(NH3 )2 (Imt)2 ](NO3 )2 (1 ) and trans -[Pt(NH3 )2 (Me2 Imt)2 ](NO3 )2 (3 ) were determined by X-ray crystallography. The structures of1 and3 consist of trans -[Pt(NH3 )2 L2 ] 2+ complex ions and nitrate counter ions. The platinum atom in both the complex ions adopts a distorted square planar geometry. The spectroscopic data indicated the coordination of thione ligands to platinum(II). The in vitro cytotoxicity of these compounds as well as of cisplatin and carboplatin was investigated using MTT assay against three human cancer cell lines, which are; A549 (lung carcinoma), MCF-7 (breast carcinoma) and HTC15 (colon cancer). The in vitro cytotoxicity in several cases is comparable or even higher, than carboplatin and in two cases than cisplatin.